Arqueologia da margem Porto Alegre : a formação de uma cidade portuária (do século XVIII a meados do século XIX) - Lazzarotti, Marcelo dos Santos (2013)
Porto Alegre, a city that grew out of a port and developed in close relationship with the browsing activities, had turned its edge over the eighteenth and nineteenth centuries by those activities, which left under layers of landfill, concrete and current city asphalt, material traces that witness the everyday aspects of a port town that no longer exists. This dissertation focuses on the study of the constitution and the transformations undergone by the port area of the city of Porto Alegre eighteenth century to the mid nineteenth century. The study seeks, through the intersection of information obtained in archaeological research and information obtained in documentary written and iconographic sources, reveal the physical changes undergone by the coast of the city and the activities that conditioned these changes